Efficacy of immune checkpoint inhibitor combination therapy prior to nephrectomy in advanced renal cell carcinoma: A retrospective pilot study - Sho Kiyota; Takashi Yoshida; Takahiro Nakamoto; Eri Jino; Takao Mishima; Hidefumi Kinoshita (BJUI Compass)
Abstract Renal cell carcinoma (RCC) affects 10%–20% of patients annually, often with metastases present. This study evaluated the impact of systemic therapy before nephrectomy in patients with unresectable or metastatic renal cell carcinoma (RCC). Patients receiving upfront immune checkpoint inhibitor (ICI) combination therapy showed significantly improved progression‐free survival (PFS) compared to nephrectomy alone (2‐year PFS: 62.3% vs. 17.4%; p = 0.036), while upfront tyrosine kinase inhibitor (TKI) therapy did not (2‐year PFS: 18.2% vs. 12.3%; p = 0.545). Surgery‐related outcomes did not differ significantly between groups. ICI therapy maintained tumour reduction rates better than TKI therapy. The study highlights the potential benefits of ICI combination therapy over TKI therapy in advanced RCC, suggesting further research is needed to confirm these findings.